2013
DOI: 10.1785/0120130122
|View full text |Cite
|
Sign up to set email alerts
|

A Lithospheric Attenuation Model of North America

Abstract: Recent moderate-sized, but strongly-felt, earthquakes in eastern and central North America have highlighted the important role of the earth's attenuation structure in estimating and predicting local and regional ground motions. Over the past several years, we have been developing methods to use the amplitudes of regional phases Pn, Pg, Sn, and Lg to invert for the crust and upper mantle attenuation structure in Eurasia, and have recently started transporting the methodology to North America. We now have path c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 30 publications
1
38
0
Order By: Relevance
“…Because of the insufficient distance range and bandwidth, we fix Qf and R C . We constrained Qf to be 200 × f 0:68 from the Erickson et al (2004) model for the Basin and Range (which is also similar to Beck et al, 2013;Pasyanos, 2013;Phillips et al, 2013). This Qf model is consistent with geometrical spreading of 1=R 0:5 for that province.…”
Section: Bb Approachsupporting
confidence: 61%
See 1 more Smart Citation
“…Because of the insufficient distance range and bandwidth, we fix Qf and R C . We constrained Qf to be 200 × f 0:68 from the Erickson et al (2004) model for the Basin and Range (which is also similar to Beck et al, 2013;Pasyanos, 2013;Phillips et al, 2013). This Qf model is consistent with geometrical spreading of 1=R 0:5 for that province.…”
Section: Bb Approachsupporting
confidence: 61%
“…In Figure 7b, we illustrate this Q range as Pasyanos. In contrast, for the Colorado plateau (including northern Arizona), Pasyanos (2013) estimated Q in the 2000-5000 range for 6-12 Hz (which yields 6000 if we extrapolate to 16 Hz). Phillips et al (2013) find Q Lg between 500 and 1200 for 6-12 Hz (marked as Phillips range in the figure) for southern Arizona.…”
Section: Combining the As And Ds Approachmentioning
confidence: 90%
“…The synthetics from the three methods are compared with observations using several metrics including: (1) the character of time-domain waveforms; (2) overall Fourier and response spectral bias (from 0.1 to 10 Hz); (3) residuals for GMRotI50 PGA, PGV, and PSA at various periods; and (4) the mean USGS2014-GridSrc GMPE for the eastern United States. The comparison shows that the three methods can provide acceptable estimations for periods less than 2 s. The systematic underestimation of data to the northeast of the epicenter may be the result of local site effects or propagation path effects as suggested by Catchings et al (2012), Pasyanos (2013), andMcNamara et al (2014). The synthetics for the three methods show a similar fall-off with distance to the estimates by the USGS2014-GridSrc GMPE and comparable PGA and PSA amplitudes only for the physicsbased and stochastic site-based models.…”
Section: Discussionmentioning
confidence: 73%
“…This azimuthal dependence of amplitudes has been attributed to an increase in ground motion to the northeast of the epicenter caused by fault-guided waves and Moho reflections amplified by a shallowing Moho to the northeast (Catchings et al, 2012). In addition, azimuthally dependent attenuation (Pasyanos, 2013;McNamara et al, 2014) and rupture directivity to the northeast (Hartzell et al, 2013) may also be factors. This discrepancy is not as obvious in the stochastic site-based synthetics, except for the longest period of 5.0 s, because we have chosen the synthetic that most closely matches the data out of 50 realizations at each station and the breadth in amplitudes between the realizations is sufficient to absorb the azimuthal differences.…”
Section: Orientation-independent Intensity Measuresmentioning
confidence: 99%
“…The value for Q 0 varies regionally and is about 650-1000 for CENA (Mitchell and Hwang, 1987;Erickson et al, 2004;Pasyanos, 2013). Based on my previous tests (Graizer, 2014a), I concluded that it is reasonable to use a constant Q Q 0 typical for a given region/ path (usually that for Lg or coda waves).…”
Section: Anelastic Attenuationmentioning
confidence: 99%